Global temporal patterns in plant nutrient resorption plasticity. Issue 6 (14th February 2019) - Drenovsky, Rebecca E.; Pietrasiak, Nicole; Short, Thomas H.
Abstract: Aim: Leaf nutrient resorption is a key nutrient conservation trait, which also influences nutrient cycling rates and pools. Most global biogeochemical models assume that resorption is non‐varying at a temporal scale. However, this trait can differ substantially within populations among years. We assessed the commonality of attaining proficient resorption, the factors associated with proficient resorption, as well as the variability of this trait and the factors controlling trait variability. Location: Global. Time period: 1965–2009. Major taxa studied: Plants. Methods: We compiled multi‐year nutrient resorption data from the literature, representing 50 studies, 94 unique study locations, and 141 species from 53 families and 29 orders. We used multiple linear regression to relate resorption data, as well as the variability in this trait, expressed as the coefficient of variation, to environmental factors. Results: Resource availability was a key driver of resorption, with nutrient‐poor soils associated with more complete resorption and lower resorption plasticity. Nitrogen and phosphorus resorption differentially responded to some drivers, such as leaf habit, soil order and mycorrhizal status. Main conclusions: Overall, environmental and biological factors representing a strong selective force for nutrient conservation, such as nutrient‐poor soil orders, semi‐arid soil moisture regimes, or lack of plant mutualists, were associated with complete resorption, whereas incomplete resorption was associated with weak selective forces, such as nutrient‐rich soil orders, or factors impeding this physiological process (e.g., drought). Inter‐annual variability in resorption was common, particularly for phosphorus. This plasticity has implications for ecosystem nutrient cycling and plant productivity, and accounting for this plasticity in dynamic models of nutrient cycling will improve predictions of nutrient limitations and productivity under future climate conditions.